2022
DOI: 10.47836/pjtas.45.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Rumen Fluke in Cattle and Buffaloes in Asia: A Review

Abstract: Rumen fluke is a parasitosis that infects ruminant animals across a wide geographical range of countries. It is a severe infection in temperate and tropical climate regions of Asia, Australia, Africa, and Europe, which cause significant economic losses. In this review, the available information to date on rumen fluke species infecting cattle and buffaloes in Asian countries is evaluated. The citation search was performed through specific keywords, literature published from 1964 to 2021, retrieved from electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…African buffalo was the most frequently infected wild ruminant across Africa, infected with 21 amphistome species from different genera which include Calicophon , Carmyerius, Cotylophoron, Paramphistomum, Gigantocotyle, Leiperocotyle and Stephanopharynx . A similar trend was observed in Asian countries (Bangladesh, China, India, Indonesia, Iraq, Iran, Japan, Malaysia, Nepal, Pakistan, Phillipines, Sri Lanka, Thailand, Turkey), where over 26 amphistome species belonging to the families Gastrothylacidae and Paramphistomoidea were reported in buffaloes ( Tookhy et al, 2022 ). These infections in African buffalo are not surprising as these ruminants are widely distributed across sub-Saharan Africa, and is often considered an important reservoir for livestock diseases ( Eygelaar et al, 2015 ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…African buffalo was the most frequently infected wild ruminant across Africa, infected with 21 amphistome species from different genera which include Calicophon , Carmyerius, Cotylophoron, Paramphistomum, Gigantocotyle, Leiperocotyle and Stephanopharynx . A similar trend was observed in Asian countries (Bangladesh, China, India, Indonesia, Iraq, Iran, Japan, Malaysia, Nepal, Pakistan, Phillipines, Sri Lanka, Thailand, Turkey), where over 26 amphistome species belonging to the families Gastrothylacidae and Paramphistomoidea were reported in buffaloes ( Tookhy et al, 2022 ). These infections in African buffalo are not surprising as these ruminants are widely distributed across sub-Saharan Africa, and is often considered an important reservoir for livestock diseases ( Eygelaar et al, 2015 ).…”
Section: Discussionsupporting
confidence: 71%
“…In general, results showed that Southern African countries recorded some of the highest prevalence rates of amphistomes infections, while East, North, and Central Africa have low to moderate rates. Regional differences in amphistome prevalence are likely due to factors like environmental conditions, ecology, host-parasite interaction, and collection season ( Phiri et al, 2011 ; Tookhy et al, 2022 ). According to ( Hajipour et al, 2021 ) this variation in prevalence of amphistomes may due to different climatic conditions, ecological and management systems.…”
Section: Discussionmentioning
confidence: 99%
“…PP are the most common trematodes found in the rumen and reticulum of ruminants. Evidence of its infection has been reported worldwide, especially in Asia (61.5%) [ 15 ]. Typically, mature rumen flukes do not induce clinical disease, but substantial infection with immature parasites can result in enteritis accompanied by symptoms such as diarrhea, anorexia, and dehydration, which may result in mortality among young livestock [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Freshwater snails play an important role as intermediate hosts of several trematodes species in the superfamilies such as Paramphistomoidea, Fascioloidea, Clinostomoidea, Diplostomoidea, Echinostomatoidea, Pronocephaloidea and Schistosomatoidea (Bawm et al 2022; Martin & Cabrera, 2018;Islam et al 2013). These trematodes parasites in many tropical and sub-tropical countries cause public health threats and socioeconomic problems (Tookhy et al 2022;Prasopdee et al 2015). Family Lymnaeidae receives much interest among freshwater snails since they are involved in the life cycle of several trematodes with substantial biomedical and veterinary implications (Saijuntha et al 2021;Mohammed et al 2016; Bargues et al 2011).…”
Section: Introductionmentioning
confidence: 99%